Perceptions of disinformation regulation in the Andean community - Suing, Abel (Frontiers in Communication, 2024)
Disinformation generates political polarisation and affects the quality of democracy, so understanding attitudes towards the regulation of disinformation will help society and its leaders to develop effective and inclusive approaches to combat this phenomenon. The purpose of the research is to determine the perceptions and propensities of Andean Community citizens regarding the regulation of disinformation. Bolivia, Colombia, Ecuador and Peru have formed a political and economic bloc since 1969, and are subscribers to the Inter-American legal framework. The methodology is quantitative and qualitative, with exploratory and descriptive approaches. The instruments used are a survey, focus groups and expert interviews with experts, which were applied between July 2022 and May 2024, to establish trends and to avoid biases. It was found that 80% of respondents and participants in the focus groups agreed that misinformation alienates people from democratic representation and there was evidence of distrust in elections. A vision of regulation by states persists, through laws, rather than selfor co-regulation. The discussion revolves around the need for a multifaceted approach to combat disinformation, between regulation, media literacy and the responsibility of digital platforms, without compromising freedom of expression.